Women Playwrights of Early Modern Spain [Reseña] - Vizán Rico, Blanca (Revista de Escritoras Ibéricas, 2017)
Enríquez de Guzmán, Feliciana; Ana Caro Mallén y sor Marcela de San Félix, Women Playwrights of Early Modern Spain, Nieves Romero-Díaz and Lisa Vollendorf (eds.), Harley Erdman (trad.), Toronto ; Tempe: Ontario Iter Press ; Arizona Center for Medieval and Renaissance Studies , 2016, 272 pp. (The Other Voice in Early Modern Europe. The Toronto Series, 49; Medieval and Renaissance Texts and Studies 501) ISBN 978-0866985567